1977
DOI: 10.1002/bjs.1800640304
|View full text |Cite
|
Sign up to set email alerts
|

Pulsion intubation for palliation of carcinoma of the oesophagus

Abstract: One hundred and eighty-one patients with carcinoma of the upper thoracic oesophagus were intubated perorally using a Procter-Livingstone tube. The mortality was 16-6 per cent but, in the patients who survived, the palliation achieved, as judged by improved swallowing, was considered satisfactory. Factors influencing the success of intubation are also considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The mean survival time for the 15 patients malignant stricture in the esophagus or car& were intu-who survived the Postoperative period ranged between bated with a Celestin tube [Celestin, 19591. All tumors 27 and 291 days (mean 125 days). were considered unresectable either because of tumor All complications are presented in [Palva et al, 1974;Hegarty et al, 1977;Lishman et al, 1980;Watson, 19821. The complication rate is considered higher after surgical than after endoscopic intubation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean survival time for the 15 patients malignant stricture in the esophagus or car& were intu-who survived the Postoperative period ranged between bated with a Celestin tube [Celestin, 19591. All tumors 27 and 291 days (mean 125 days). were considered unresectable either because of tumor All complications are presented in [Palva et al, 1974;Hegarty et al, 1977;Lishman et al, 1980;Watson, 19821. The complication rate is considered higher after surgical than after endoscopic intubation.…”
Section: Resultsmentioning
confidence: 99%
“…Intubation of the esophagus is considered by most patients the most acceptable method for palliation. In many studies [Das and John, 1973;Sanfelippo and Bernatz, 1973;Girardet et al 1974;Thomas, 1974, Hegarty et al, 1977Atkinson et al, 1978;Gallagher et al, 1978;Den Hartog Jager et al, 1979, Saunders, 1979Watson, 19821 the improved quality of life after intubation of the esophagus has been documented. We could in this study report on relief of dysphagia in two-thirds of our patients, which is in agreement with previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…gr0ups3,S-8, [10][11][12][13][14]16,[20][21][22][23][24][25][26][27][28][29] ments (surgery, radiation therapy, and chemotherapy, used alone or in combination) have failed. Of the 12 main factors evaluated in our study, only two appear to have prognostic significance: patients with stenosis less than 7 mm, and patients with stenosis located at the lower third and cardia.…”
Section: Discussionmentioning
confidence: 99%
“…The Negus oesophagoscope was then passed for visualisation and biopsy of the stricture (benign strictures of the oesophagus were excluded from the study). Antegrade dilatation of the stricture and intubation with the modified Proctor-Livingstone tube (Latex Products, Johannesburg) was carried out as described by Hegarty et al 8 Aspiration of acid onto litmus paper via a nasogastric tube confirmed correct placement of the endooesophageal prosthesis and free passage into the stomach. Repeat dilatation was attempted after three days if the first attempt had to be abandoned.…”
Section: Methodsmentioning
confidence: 99%